Penerapan Big Data Analytic Terhadap Strategi Pemasaran Job Portal di Indonesia dengan Karakteristik Big Data 5V - Rima Tamara Aldisa; Pandu Maulana; Mohammad Aldinugroho Abdullah (Universitas Budi Darma, 2022)
The impact of the COVID-19 pandemic has paralyzed the business sector, resulting in changes in business activities in many companies today. Many companies are competing to digitize their business, PT XYZ is one of them. PT XYZ is a company engaged in outsourcing. Outsourcing companies are one of the many types of companies that have been heavily impacted during the COVID-19 pandemic. In order to restore its business, PT XYZ has an innovation in the form of a job portal. PT XYZ always strives to market its job market. This is the biggest challenge that PT XYZ has on its job portal. Therefore, it is necessary to apply big data to be utilized by PT XYZ. This study reviews the application of big data on the job portal of PT XYZ. The implementation of big data refers to the five characteristics of big data (5V), volume, variety, velocity, veracity, and value. The method used to obtain data in this study is through interviews and observation. The results of this study indicate that the five characteristics meet the criteria for the application of big data. This allows PT XYZ's job portal to apply big data analytics to its marketing strategy.